Musculotendinous system of mesopelagic fishes: Stomiiformes (Teleostei). Issue 6 (19th December 2021) - Schnell, Nalani K.; Kriwet, Jürgen; López‐Romero, Faviel A.; Lecointre, Guillaume; Pfaff, Cathrin
Abstract: Every night the greatest migration on Earth starts in the deep pelagic oceans where organisms move up to the meso‐ and epipelagic to find food and return to the deeper zones during the day. One of the dominant fish taxa undertaking vertical migrations are the dragonfishes (Stomiiformes). However, the functional aspects of locomotion and the architecture of the musculotendinous system (MTS) in these fishes have never been examined. In general, the MTS is organized in segmented blocks of specific three‐dimensional 'W‐shaped' foldings, the myomeres, separated by thin sheets of connective tissue, the myosepta. Within a myoseptum characteristic intermuscular bones or tendons may be developed. Together with the fins, the MTS forms the functional unit for locomotion in fishes. For this study, microdissections of cleared and double stained specimens of seven stomiiform species ( Astronesthes sp., Chauliodus sloani, Malacosteus australis, Eustomias simplex, Polymetme sp., Sigmops elongatus, Argyropelecu s affinis ) were conducted to investigate their MTS. Soft tissue was investigated non‐invasively in E. schmidti using a micro‐CT scan of one specimen stained with iodine. Additionally, classical histological serial sections were consulted. The investigated stomiiforms are characterized by the absence of anterior cones in the anteriormost myosepta. These cones are developed in myosepta at the level of the dorsal fin and elongate gradually in more posterior myosepta. In all but one investigated stomiiform taxon the horizontal septum is reduced. The amount of connective tissue in the myosepta is very low anteriorly, but increases gradually with body length. Red musculature overlies laterally the white musculature and exhibits strong tendons in each myomere within the muscle bundles dorsal and ventral to the horizontal midline. The amount of red musculature increases immensely towards the caudal fin. The elongated lateral tendons of the posterior body segments attach in a highly complex pattern on the caudal‐fin rays, which indicates that the posterior most myosepta are equipped for a multisegmental force transmission towards the caudal fin. This unique anatomical condition might be essential for steady swimming during diel vertical migrations, when prey is rarely available. Abstract : The musculotendinous system (MTS) of the trunk of fishes forms together with their fins the functional unit of locomotion. Micronektivore fishes of the oceanic mesopelagic zone, like, e.g. Stomiiformes, display the largest migration on earth during the night. We investigated the morphology of the MTS in stomiiforms and highlight anatomical differences between diel vertical migrators and non‐migrators.